2016
DOI: 10.2217/bmm-2016-0181
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Role of Pretreatment Platelet-to-Lymphocyte Ratio as Predictors in Patients With Colorectal Cancer: A Meta-Analysis

Abstract: This meta-analysis indicated that pretreatment PLR may be a cost-effective and noninvasive serum biomarker for poor prognosis for patients with CRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…23 The NLR, PLR and LMR are the most commonly used indicators of systemic inflammatory response and have been reportedly associated with poorer outcomes in CRC patients. 12,24,25 Kilincalp et al analyzed 144 CRC patients and found that the preoperative NLR and PLR were significantly higher in the CRC patients than in 143 age-matched and sexmatched healthy participants, which suggested that the NLR and PLR might be used as potential biomarkers for the detection and monitoring of CRC. 16 Our study indicated the same result that patients with CRC had elevated NLRs and PLRs compared to those in healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…23 The NLR, PLR and LMR are the most commonly used indicators of systemic inflammatory response and have been reportedly associated with poorer outcomes in CRC patients. 12,24,25 Kilincalp et al analyzed 144 CRC patients and found that the preoperative NLR and PLR were significantly higher in the CRC patients than in 143 age-matched and sexmatched healthy participants, which suggested that the NLR and PLR might be used as potential biomarkers for the detection and monitoring of CRC. 16 Our study indicated the same result that patients with CRC had elevated NLRs and PLRs compared to those in healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue specimens allow for the direct examination of tumor and stromal cells. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Although the association between these markers and HNSCC prognosis has been investigated, the results have been inconsistent. However, blood samples can easily be obtained at any time, and blood markers can be measured repeatedly.…”
Section: Introductionmentioning
confidence: 99%
“…14 Platelet count and plateletlymphocyte ratio (PLR) are hematologic makers that have shown prognostic abilities across many types of cancers. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Although the association between these markers and HNSCC prognosis has been investigated, the results have been inconsistent. [34][35][36][37][38][39][40][41][42][43][44][45][46] Among these studies, only 1 study was prospective.…”
Section: Introductionmentioning
confidence: 99%
“…Other important factors include the increase of platelet-associated inflammatory reactions, decreased antitumor response due to relative scarcity of lymphocytes, and tumoral growth and spread induced by various epithelial and endothelial growth factors secreted by circulating active platelets. 4,5,6,7,8,9,10 When the common effect of age, sex, and comorbid diseases was examined, it was found that PLR was significantly higher in patients with liver metastasis independent of these three parameters (p<0.001). The most important prognostic marker in colon cancer is cancer stage, and liver metastasis detected preoperatively corresponds to a more advanced stage.…”
Section: Discussionmentioning
confidence: 99%
“…The platelet-to-lymphocyte ratio (PLR) has been associated with poor prognosis in many cancers, including colorectal cancer. 6,8,9 Previous studies have focused on changes in PLR at different stages of colon cancer and its effect on prognosis, response to chemotherapy, and recurrence time. 4,5,6,7,8,9,10 In this study, we aimed to determine the utility of PLR at time of admission in predicting hepatic metastasis and lymph node positivity in patients who have undergone colorectal surgery.…”
Section: Introductionmentioning
confidence: 99%